An investigation into the nature, extent, and experience of collaboration between the Eden District, Western Cape Department of Health and community-based service providers - Utian, Brett (Graduate School of Business (GSB), 2018)
A major component of the primary health care (PHC) system is the delivery of health services on a community level, at the core of which is the Home and Community Based Care (HCBC) programme. This study focuses on one element of the HCBC system, namely how those involved in the administration of the community-based health component of primary health care, understand their relationship from the perspective of both the government (WCG - DoH) and the NPO service providers in the Eden District of the Western Cape. Additionally, it analyses the nature and the extent of the collaboration between the two entities. A patient referral tool was facilitated in a collaborative process to assess the ability of the two entities to strengthen their relationship. The study methodology was undertaken utilising Insider Ethnography with the researcher as a participant observer. Ten semi-structured interviews of the key stakeholders and one focus group were conducted with the staff of four non-profit (NPO) service providers operating in the Eden District and with WCG - DoH staff managing the HCBC programme. The findings reflect a substantial disconnect and imbalance in the relationship between the two entities, highlighting a top-down, transactional process at higher levels of management, in contrast to the operational relationships at the local sub-district level which are more collaborative. This disjuncture often disempowers the NPO service providers involved in the implementation of the programme. A number of recommendations regarding communication, advocacy, and innovation are proposed. Regular meetings of government, from district to provincial levels, with the NPO service providers, to strengthen collaboration by all stakeholders, are crucial.